2023
DOI: 10.3390/vetsci10010065
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disease and Injury on Faecal Cortisol Metabolites, as an Indicator of Stress in Wild Hospitalised Koalas, Endangered Australian Marsupials

Abstract: Loss of habitat, urbanisation, climate change and its consequences are anthropogenic pressures that may cause stress in koalas. Non-invasive monitoring of faecal cortisol metabolites (FCMs) can be utilised to evaluate the impact of stressors. The aim was to determine if the tetrahydrocorticosterone (50c) and cortisol enzyme immunoassays (EIAs) could be effective in measuring FCM values in wild, stressed koalas. This research included 146 koalas from the Australia Zoo Wildlife Hospital (AZWH) and 88 from a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In all, it is not uncommon to see sex-specific differences in the non-invasive monitoring of stress-related hormones [ 23 , 25 , 44 ]. For example, in black-tufted marmosets ( Callithrix penicillate ), results showed that females had an overall higher response to ACTH and saline administration compared to males [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, it is not uncommon to see sex-specific differences in the non-invasive monitoring of stress-related hormones [ 23 , 25 , 44 ]. For example, in black-tufted marmosets ( Callithrix penicillate ), results showed that females had an overall higher response to ACTH and saline administration compared to males [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although monitoring glucocorticoid metabolite concentrations non-invasively in matrixes such as urine and feces is a powerful tool, there can be dietary, species- and sex-specific differences in hormone metabolism and composition [ 22 , 23 ]. In addition, sex and individual differences in response to particular stressors may result from variation in the severity of the stress response, and the duration of the response [ 24 , 25 ]. Thus, the approach for monitoring hormone metabolite concentrations in feces and urine for a species studied for the first time must be reliably validated [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Koala mortality was recorded at the time of the event if in situ, otherwise if a koala was recaptured and either died in care or required life-saving (i.e., major) medical intervention, a mortality event was recorded at the date of recapture. We used the dates of recaptures since mortality in the wild would be assumed to occur more rapidly (though we note that the stress of capture and captivity may influence mortality outcomes 71 ). Koalas that survived or where tracking ceased early due to collar removal, loss of VHF transmitter, or lost signal were placed in the same category as koalas that survived.…”
Section: Methodsmentioning
confidence: 99%